Formation and activation of defects in films of AIVBVI compounds in the process of growing from vapor phase - Saliy, Ya.P.; Freik, I.M.; Prokopiv (Jr), V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The work has suggested an adequate model describing formation of defects in films of AIVBVI compounds in vapor-phase growth. Being based on this model, it has given an analytical description of dependences for film electrophysical parameters (concentrations n, p and mobilities µn, µp of free charge carriers) on technological factors of film growth. We have calculated concentrations of activated and inactivated defects as subject to temperature of film deposition. The developed model enables determination of entropy and enthalpy of defect formation processes.